Managing Crisis Communication Via Social Media - Špoljarić, Anja (Naše gospodarstvo/Our economy, 2021)
Social media is becoming omnipresent in everyone’s daily life, which is changing the way consumers think, act and buy. Organizations are aware of the possibil- ities that may occur from developing social media communication strategies, but oftentimes forget to predict and block negative consequences. Information spreadability and bad communication practices are the perfect trigger of a so- cial media crisis, which is why it is crucial for organizations to know what kind of communication, both internal and external, they need to implement. To explore consumers’ opinions on social media crisis communication, an online survey was conducted. 125 participants gave their insight into their expectations of the types and tone of social media messages organizations should communi- cate during a time of crisis. These findings could be used as a guideline for crisis communication planning, considering they examine what types of mes- sages consumers prefer, and which medium of communication they prefer. Even though it is recognized that crisis situations can have a huge impact on an or- ganization’s wellbeing, consumers’ perspective on crisis communication still has not been researched thoroughly.